The Sustainability of Interreligious Dialogue in Indonesia under the Phenomenon of Intolerance by Islamic Populists - Kurniawan Netanyahu; Deri Susanto (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2022)
From 2016 to 2019, mass protests were organized by the